2004
DOI: 10.1002/mrdd.20004
|View full text |Cite
|
Sign up to set email alerts
|

The neuroanatomy and neuroendocrinology of fragile X syndrome

Abstract: Fragile X syndrome (FXS), caused by a single gene mutation on the X chromosome, offers a unique opportunity for investigation of gene-brain-behavior relationships. Recent advances in molecular genetics, human brain imaging, and behavioral studies have started to unravel the complex pathways leading to the cognitive, psychiatric, and physical features that are unique to this syndrome. In this article, we summarize studies focused on the neuroanatomy and neuroendocrinology of FXS. A review of structural imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 73 publications
5
107
0
1
Order By: Relevance
“…49 and references therein). The HPA axis alterations can have wide effects on behaviors and has been attributed as being one of the main correlates of social deficits in patients with fragile X syndrome (50). Prenatal LPS exposure, which activates the fetal HPA axis (47), causes structural, neurophysiological, and functional changes in the hippocampus (e.g., refs.…”
Section: Resultsmentioning
confidence: 99%
“…49 and references therein). The HPA axis alterations can have wide effects on behaviors and has been attributed as being one of the main correlates of social deficits in patients with fragile X syndrome (50). Prenatal LPS exposure, which activates the fetal HPA axis (47), causes structural, neurophysiological, and functional changes in the hippocampus (e.g., refs.…”
Section: Resultsmentioning
confidence: 99%
“…The cerebellar vermis is a structure that is anatomically connected to the interpositus nucleus and hippocampus (Hessl et al, 2004), believed to play a role in motor behaviour, auditory processing, and language (Steinlin, 2008). Decreases in the cerebellar posterior vermis size has been found in patients with FXS (Mostofsky et al, 1998).…”
Section: The Cerebellum and Deep Cerebellar Nucleimentioning
confidence: 99%
“…Depending upon genetic background, behavioral and synaptic models of memory in mice are consistent with the human FX phenotype (For background, see Lombroso 2003;Hessl, Rivera et al 2004). Measures of learning and memory in a fear based paradigm were generally comparable for targeted and wild type alleles on a C57BL/6 background (Peier, McIlwain et al 2000), though these mice expressed reduced memory for avoidance in a leverpress paradigm compared to wild type (Brennan, Albeck et al 2006).…”
Section: Fragile X Mousementioning
confidence: 99%
“…Rolipram, 4-(3-Cyclpentyloxy-4-methoxyphenyl)-2-pyrrolidinone, is a potent PDE4 inhibitor, a class that shows clinical potential in the treatment of depression. Through cAMP-mediated mechanisms, pharmacotherapy that inhibits PDE4 is prone to increase the transcription and function (Miller, Vogt et al 2002;Pace, Hu et al 2007) of reduced numbers of FX dendritic glucocorticoid receptors (Miyashiro, Beckel-Mitchener et al 2003) involved in hypothalamic-pituitaryadrenal (HPA) regulation (Hessl, Rivera et al 2004). A clinical trial of rolipram reported acceptable tolerance levels at clinically relevant doses (Fleischhacker, Hinterhuber et al 1992).…”
Section: Camp Therapymentioning
confidence: 99%